IDENTIFIKASI TRANSFORMASI ARSITEKTUR : PASAR CINDE PALEMBANG: IDENTIFIKASI TRANSFORMASI ARSITEKTUR : PASAR CINDE PALEMBANG - Indri Astrina Wirakusumah; R.A Sunia Widiaswara; Jonathan Hans Yoas Sihotang (Ide dan Dialog Desain Indonesia (Idealog), 2026)
Abstract : This study examines the transformation of Pasar Cinde in Palembang within the architectural and environmental health context based on healthy market standards. As one of the oldest traditional markets, Pasar Cinde has undergone significant changes due to demolition and an unfinished modernization project, leading to spatial disorganization and a decline in environmental quality. This study assesses the market’s compliance with healthy market standards using an architectural anatomy approach, covering the environment, site, and buildings. The research employs a qualitative method with a descriptive-analytical approach through six stages: (1) documenting the market's condition before and after demolition, (2) classifying architectural elements, (3) comparing significant changes, (4) developing an evaluation matrix, (5) identifying the impact of transformation, and (6) drawing conclusions and recommendations. The findings indicate that Pasar Cinde’s feasibility declined from 55.5% before demolition to 20% afterward. Several key aspects were not met, including air circulation, natural lighting, drainage, cleanliness, and visitor and vendor comfort. However, there is potential for improvement in architectural aspects, such as better parking management, optimization of natural and artificial lighting, and more efficient spatial management. With the evaluation matrix, this study provides an objective assessment of the market’s post-transformation condition and offers recommendations to improve Pasar Cinde’s compliance with healthy and sustainable market principles. Keyword : Architectural anatomy, architectural transformation, healthy market, Pasar Cinde, sustainability.